The role of land management and elevation in shaping soil microbial communities: Insights from the Central European Alps. (November 2020) - Praeg, Nadine; Seeber, Julia; Leitinger, Georg; Tasser, Erich; Newesely, Christian; Tappeiner, Ulrike; Illmer, Paul
Abstract: In the last 100 years, climate warming has been affecting the European Alps faster and more severely than globally observed temperature patterns. Temperature changes are known to affect soil properties and microbial community structures, and land-use change in Europe is an expected socio-economic consequence of climate change. However, few studies have simultaneously investigated how land-use and climate-related changes shape microbial (prokaryotic and fungal) communities in this region. Therefore, here we have investigated sites within a Long-Term Socio-Ecological Research (LTSER) area in South-Tyrol (Italian Alps), characterizing soil properties and microbial communities and diversities. We investigated three important land-use types (forests, hay meadows, and pastures) at 1500 m above sea level (a.s.l.), as well as an elevational gradient (1000, 1500, and 2000 m a.s.l.) of pastures. Results showed that land-use did not lead to distinct differences in soil properties, even though the land-uses have been consistent over recent decades (30–160 years). Nevertheless, the meadow sites showed increased soil pH, soil water content, and organic matter content compared with the forest and pasture sites. As a result, the fungal soil microbiome correlated significantly with land-use and fungal diversity increased on the meadow sites, whereas prokaryotic communities were less affected by land-use and did not show significant changes in diversity patterns. Along increasing elevation, the most pronounced changes were a decrease in soil pH, and an increase in organic matter content. The influence of elevation was clearly reflected in the structures of the prokaryotic and fungal communities, with significantly lower diversities and decreased species richness at the highest studied elevation. Indicator taxa for the different land-uses and elevations were established. Russulaceae and Flavobacteriaceae were biomarker families for forests, several Mortierella spp. and Microlunatus sp. were identified as indicator species for meadows and Herpotrichiellaceae spp. and Bacillaceae spp. for pastures. For pastures, increasing elevation led to increased occurrence of Acidobacteria Gp1, Gp2 and Spartobacteria and the fungal genera Hygrocybe and Clavaria, all typical inhabitants of nutrient-poor grasslands. Changes in soil pH across the elevation gradient and according to land-use were shown to play a major role, but we would like to emphasize the complex interplay between pH, organic matter, temperature, and water content. The increased prokaryotic and/or fungal diversity observed on low-elevated pastures and meadows, respectively, is assumed to be not only an association with the changed soil pH but is likely indicative of a disturbed system or a soil site facing repeated disturbances (e.g., temperature, drought, and fertilization). Within the present study, we were able to show that elevation had a strong effect on prokaryotic and fungal communities whereas changes in land-use mainly affected fungi. Thus, the present study contributes to better predict the response of microorganisms to temperature-related future changes in the Central European Alps and could support decisions in upcoming soil management strategies. Highlights: Alpine meadows differed most clearly in terms of soil properties from forests and pastures. Elevation and elevation-dependent soil properties shaped prokaryotic and fungal communities. Land-use affected mainly the fungal microbiome. Clear indicator taxa for land-use variations and elevation were established. Disturbances (e.g. drought, fertilization) seem to increase soil microbial diversities.